The AMPK Agonist AICAR Inhibits TGF-β1 Induced Activation of Kidney Myofibroblasts - Chen, Kuan-Hsing (Public Library of Science, 2014)
Activation of interstitial myofibroblasts and excessive production of extracellular matrix proteins are common pathways that contribute to chronic kidney disease. In a number of tissues, AMP-activated kinase (AMPK) activation has been shown to inhibit fibrosis. Here, we examined the inhibitory effect of the AMPK activator, 5-aminoimidazole-4-carboxyamide ribonucleoside (AICAR), on renal fibrosis in vivo and TGF-β1-induced renal fibroblasts activation in vitro. A unilateral ureteral obstruction (UUO) model was induced in male BALB/c mice. Mice with UUO were administered AICAR (500 mg/Kg/day) or saline intraperitoneally 1 day before UUO surgery and daily thereafter. Both kidneys were harvested 7 days after surgery for further analysis. For the in vitro studies, NRK-49F rat fibroblasts were pre-incubated with AICAR before TGF-β1 stimulation. The inhibitory effects of AICAR on signaling pathways down-stream of TGF-β1 were analyzed. In UUO model mice, administration of AICAR attenuated extracellular matrix protein deposition and the expression of α-smooth muscle actin (α-SMA), type I collagen and fibronectin. Pre-incubation of NRK-49F cells with AICAR inhibited TGF-β1-induced myofibroblast activation. Silencing of AMPKα1 by siRNA or by blocking AMPK activation with Compound C diminished the inhibitory effect of AICAR. Moreover, the inhibitory effects of AICAR on TGF-β1-mediated myofibroblast activation were associated with down-regulation of ERK 1/2 and STAT3. Our results suggest that AICAR reduces tubulointerstitial fibrosis in UUO mice and inhibits TGF-β1-induced kidney myofibroblast activation. AMPK activation by AICAR may have therapeutic potential for the treatment of renal tubulointerstitial fibrosis.